Genus: Strelitzia - Vieira, Marcos Ribeiro da Silva [UNESP]; Lima, Giuseppina Pace Pereira [UNESP]; Medeiros, Damiana Cleuma de; Souza, Ângela Vacaro de [UNESP]; Oliveira, Emídio Cantidio Almeida de (Academic Journals, 2012)
This review aimed to show the importance of Strelitzia in Floriculture. The genus named after the duchy of Mecklenburg-Strelitz, birthplace of Queen Charlotte of United Kingdom. A commom name of the genus is bird of paradise flower, because of a supposed resemblance of its flowers to the bird of paradise. In this context, it is currently a growing interest in exotic cultures, with tropical characteristics, such as species of the family Strelitziaceae. Thus, it was observed that the production of agricultural activity, Strelitzia is one of increasing social and economic importance in the world.
Keywords: Zingiberales; Strelitziaceae; Cut flower; Inflorescence